Detecting a Literary Future in the Historical Past: The Gibraltar Case - Stotesbury, John A. (Armenian Folia Anglistika, 2015)
Until the present millennium, very little creative literary writing in either English or Spanish had been published in the British colonial enclave of Gibraltar. Given the small population size of the autonomous community of some 30,000 people, it was considered unlikely that a “national” literary culture could form. In the course of the past decade, a handful of dedicated writers have published a noticeable amount of fiction, all of which is concerned with establishing a recognized Gibraltarian literary identity. The present article, while not arguing for the permanence of a Gibraltarian national literary culture, attempts to trace some of the ways in which a small, unified, geopolitical territory has attempted to tell its own story.
Keywords: Gibraltar; identity; historical crime fiction; siege; memory; postcolonial; museumification